Analisis Pengambilan Keputusan (Decision Making) Atlet Petanque Pada Situasi Kritis Pertandingan - Agung Prasetyo; Irawan, Safri; Rifky Mile; Meri Haryani; I Kadek Suardika; Arief Ibnu Haryanto; Sri Wicahyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the decision-making of petanque athletes in critical match situations in Gorontalo Province. Decision-making is a crucial aspect of petanque because it is determined not only by technical ability but also by the athlete's cognitive, tactical, and psychological abilities in interpreting game situations. This study used a quantitative descriptive approach, with a sample of 20 petanque athletes selected using a total sampling technique. The research instrument was a Likert-scale questionnaire consisting of 20 items with indicators of situation reading, tactical understanding, alternative course of action selection, decision accuracy and speed, self-confidence, pressure control, and decision evaluation. Data were analyzed using descriptive statistics in the form of averages, percentages, and categories. The results showed that the decision-making level of petanque athletes was in the good category with an average percentage of 79.25%. The highest indicator was the ability to interpret match situations, while the lowest indicator was pressure control. The conclusion of this study indicates that athletes have good decision-making skills in critical match situations, but still need improvement in the aspects of pressure control and decision-making speed to optimize athlete performance in stressful match conditions.